The Dynamics of the Employee Branding Effect: The Valuation of Interpersonal Relationships in Organizational Results - Sousa, Andrea I. O. C.; Thomaz, João P. C. F. (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
The contribution of mentoring (Kram, 1983, 1985; Kram, & Isabela, 1985; Ragins, & Kram, 2007) and of helping relationships (Schein, 1999, 2009, 2013), when introduced in the employee branding model (Miles, & Mangold, 2004, 2005), as amplifiers of social relationships in organizations, leads to a new and increased result, the Employee Branding Effect process that contributes to a real and concrete diagnosis of the organization’s relational and organizational environment. The Employee Branding Effect promotes and reinforces the psychological contract between employees and the organization through the increase of catalyzing actions of the domain of interpersonal relationships that result from the informality created in social exchanges inside and outside of the organizations, with a change in the focus from management by objectives (Wang, & Wong, 2011) to management by competencies, meaning, from Organizations to the People, based on the leadership exercise evolution (Wang, & Wong, 2011) influencing the organization’s brand image (Lishan, & Yaoqi, 2011). The study was conducted in 2015 and involved 30 organizations and 725 employees who answered a questionnaire with 79 statements to measure the Employee Branding Effect. This study allowed the validation and reliability of the developed instrument, but also to demonstrate statistically the moderating effect of mentoring and helping relationships, from the informal to the formal domain of organizations, and to confirm a positive increase in the results of the employee branding process when enhanced and promoted by actions within the scope of interpersonal relationships. This research required the combined and scientifically correct use of more than one methodology or parts of methodologies, using a multimethodological enrichment procedure due to the integration and interaction of several complex concepts of the behavioral and organizational domain, creating a new paradigm in the organization’s management (Mingers, & Gill, 1997). The Employee Branding Effect process reveals important analysis factors that allow a clear observation of the organizational reality, especially regarding the greater comprehensiveness and empowerment of social relationships in the sustainability of organizations, with an integrated vision of Human Resources Management and Organizational Behavior dynamics, based on the social exchange relationships of Relationship Marketing.